Measurement Based Statistical Channel Characterization of Air-to-Ground Path Loss Model at 446MHz for Narrow-Band Signals in Low Altitude UAVs - Ede, Burak; Yarkan, Serhan; Ekti, Ali Riza; Baykas, Tuncer; Cirpan, Hakan Ali; Gorcin, Ali (IEEE, 2020)
Powered by the advances in microelectronics technologies, unmanned aerial vehicles (UAVs) provide a vast variety of services ranging from surveillance to delivery in both military and civilian domains. It is clear that a successful operation in those services relies heavily on wireless communication technologies. Even though wireless communication techniques could be considered to reach a certain level of maturity, wireless communication links including UAVs should be regarded in a different way due to the peculiar characteristics of UAVs such as agility in 3D spatial domain and versatility in modes of operation. Such mobility characteristics in a vast variety of environmental diversity render links including UAVs different from those in traditional, terrestrial mobility scenarios. Furthermore, UAVs are critical instruments for network operators in order to provide basic voice and short messaging services for narrow band communication in and around disaster areas. It is obvious that such widespread use of UAVs under different scenarios and environments requires a better understanding the behavior of the communication links that include UAVs. Therefore, in this study, details of a measurement campaign designed to collect data for large-scale propagation characterization of air-to-ground links operated by UAVs at 446MHz under narrowband assumption are given. Data collection, post-processing, and measurement results are provided.
Keywords: UAV; Channel Modeling; Measurements; Path Loss; Automation & Control Systems; Computer Science; Telecommunications; Transportation